Corporate governance : the Indian scenario / Vasudha Joshi. - Joshi, Vasudha (Foundation Books, 2004)
Corporate governance is part of an economy's system which has today become the most important mechanism for resource allocation. It is affected by capital market, block holders, institutional investors, proxy wars, company law and capital market regulations, and many other macro-economic as well as political factors. Historical evolution of corporate governance naturally has a bearing on current developments. This book is an attempt to weave these factors together coherently. Much of the concerned literature revolves around the agency problem, while in developing countries expropriation of small shareholders is the governance problem. However, shareholder activism is not likely to resolve the issue. Many more measures, from audit committees of the board, rigorous disclosures, exercise of voting rights by institutional investors, strict monitoring by capital market regulator to takeover bids are required to ensure corporate accountability.